العوامل المؤثرة في تقبل الفصول الافتراضية لدى طلبة كلية التربية الأساسية بالكويت في ضوء نموذج قبول التقنية TAM - قحطاني، سعيد سعد محمد مانع (Kulliyah of Education, International Islamic University Malaysia, 2021)
The successful use of technology in education is relies primarily on the satisfaction and acceptance of its beneficiaries. This research aims to reveal the factors influencing the understanding of students of Faculty of Education in Kuwait for the virtual classrooms in the light of their acceptance for the TAM model. Survey methodology and selection of 400 students from Faculty of Education in Kuwait as a sample during the first semester in the academic year 2018-2019 are two methods used to achieve the goals of the research and test its hypotheses. The research develops a questionnaire consists of three major parts. After collecting and analysing the data statistically, the results proves that there is a positive impact of the relationship between the intent of using virtual classrooms, usefulness factors and the ease of using technical education in virtual classrooms for the students in Faculty of Education in Kuwait. The research also shows that there is a positive impact of the relationship betweet the independent factors such as (technical support, interactions in teaching and self-efficacy) and the usefulness and the ease of using technical education in virtual classrooms for the students. Another positive impact of the relationship is discussed by this research connects the independent factors (technical support, interactions in teaching and self-efficacy), the students' intention of using the virtual classrooms through the usefulness and the ease of use as a feedstock for them. Besides, it is indicated that the gender of the students has no effection in their acceptance for using the information technology in virtual classrooms however the experience palys a vital role in that. The research concludes with a mention of some applied recommendations for the results of this research.